Implementation of ABSS Accounting in CV One Solution Media's Financial Statements (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2020)
Financial reports used in CV. One Solution Media is still done manually, namely making financial reports by recording books on paper or books so that companies often lose proof of transactions and calculations or records that are not in accordance with accounting standards, making the amount of assets, capital or debt in the company not clear, as well as reports the resulting incomplete, there is no balance sheet and changes in the company's capital is also less strict in managing transaction evidence, and requires an accounting information system to create complete, neat, timely presented financial reports and according to accounting standards Cash-based accounting recording systems (Cash Basis), and inventory recording systems using the Perpetual Method. The application used in this research is ABSS Accounting. The research begins with manual and computerized transaction data management, then an analysis is carried out to find a difference. The results of this study indicate that the financial reports generated from manual recording or recording with the ABSS Accounting application are in accordance with accounting standards, but making accounting reports using ABSS Accounting is faster than manual accounting and the risk of experiencing calculation errors is smaller. The purpose of this research is to create quality financial reports for the company, effective, efficient, and in accordance with accounting standards. So that it is beneficial for the company in internal control and support in making decisions.